An Adaptive Constraint Method for Paraunitary Filter Banks with Applications to Spatiotemporal Subspace Tracking. (17th October 2006) - Douglas Douglas, Scott C. Scott C.
Abstract : This paper presents an adaptive method for maintaining paraunitary constraints on direct-form multichannel finite impulse response (FIR) filters. The technique is a spatiotemporal extension of a simple iterative procedure for imposing orthogonality constraints on nearly unitary matrices. A convergence analysis indicates that it has a large capture region, and its convergence rate is shown to be locally quadratic. Simulations of the method verify its capabilities in maintaining paraunitary constraints for gradient-based spatiotemporal principal and minor subspace tracking. Finally, as the technique is easily extended to multidimensional convolution forms, we illustrate such an extension for two-dimensional adaptive paraunitary filters using a simple image sequence encoding example.